NORMALISASI BANJIR KANAL TIMUR DAN RELOKASI RUMAH PENDUDUK (Studi Tentang Perubahan Sosial Dan Politik Kampung Nelayan Tambakrejo Semarang) - Wati, Furia Hera; Adnan, Muhammad -; -, Supratiwi - (Journal of Politic and Government Studies, 2024)
he construction of the Semarang East Canal Flood Normalization project by the Semarang City Government in 2019 caused people living on the riverbanks to be relocated to the row houses of Tambakrejo Fisherman Village Semarang. The community has gone through a long process before finally succeeding in occupying the row house that they have occupied for approximately 2.5 years. This study aims to analyze social changes and political attitudes of the community after relocation along with the positional and negative impacts of these changes. This research adopts Himes and Moore's theory of dimensions of social change and the attitudinal change component of Gordon W. Alport. This study used qualitative research methods by combining data based on the results of interviews and observations. The results showed that after being relocated, the people of RT 06 RW 16 Tambakrejo Fisherman Village had experienced social and political changes in their lives. Structurally, people have undergone a change in roles that cause them to be more recognized in society because they occupy several social roles in their environment. Culturally, many new cultures entered that were able to empower and improve people's living habits. Then, interactionally people have experienced increased interaction so that their relationships are getting closer. Likewise, the political attitude of the people towards the Semarang City Government which has also changed to be much more trusting, satisfied, and actively participating in overseeing government work programs related to welfare because previously they were skeptical of the government's role because they felt marginalized. The existing changes have a positive impact, namely reducing social conflicts between citizens, people are increasingly empowered in knowledge and experience, and increasing community welfare due to improving economic conditions. However, these changes turned out to have negative impacts such as social jealousy, conflicts of interest, and reduced willingness to work together to fight for their rights that have not been achieved, namely the right to home ownership which until now is still being pursued with the LBH Semarang City and WALHI Central Java. To overcome this, the community needs to redetermine in pursuing their rights, and the Semarang City Government should be able to easily provide ownership rights to houses occupied by the community by putting aside personal interests or groups